Papua New Guinea : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Papua New Guinea. (IMF Staff Country Reports; Country Report ;, 2006)
Papua New Guinea's 2005 Article IV Consultation reports that the economy continues to perform well as the recovery maintains its momentum and the authorities adhere to disciplined fiscal and monetary policies. The central government budget has been estimated to be once more in surplus in 2005, as mining and petroleum revenue remain strong and overall expenditure is kept in check, resulting in a further reduction in public sector debt. Monetary policy has achieved a favorable combination of relatively low interest rates and inflation.